CORRELATION OF CARCASS CHARACTERISTICS AND TESTIS MEASUREMENTS OF THE INDIGENOUS COCKS IN THE SEMI ARID ZONE OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
The current study was conducted to evaluate the association between the body weight, carcass  characteristics and the testis measurements of the three matured cocks of about one year to one and half months of age in the semi arid zone of Nigeria. Sixty matured cocks were used for the study with twenty from each of the genotype. The data collected on the carcass characteristics of the three genotypes of cocks were analyzed using SPSS Version 21 Statistical tool. Differences between treatments means were separated using Duncanâ€™s Multiple Range Test of the same software. The correlations between the different variables were determined using Pearson correlation. The results showed a positive correlation (P< 0.05) between live weight and the internal organs. Also positive significant (P
Keywords: Carcass weight, Genotype, Testis measurements, Indigenous cocks